Representation of African cultural knowledge and identity in versions of German-translated things fall apart by Chinua Achebe—a critical intercultural communication analysis (2022)
The translation of Things Fall Apart (TFA) into German has elicited interest in language interaction and especially in German-African textual intercultural communication within broader Euro-African cultural and postcolonial relations. The publication of a third German translation of TFA, Alles Zerfällt, in 2012 by Uda Strätling promises an alternative reading and possibly a truer representation of African cultural knowledge and identity compared to the two previous translations. Drawing on I.A. Richards’ theory of meaning, skopos theory, and postcolonial theory, this study examines, through a critical intercultural analysis of purposively selected cultural text units, the transfer of African cultural knowledge from the source text to the target texts in order to elucidate how African cultural identity is represented to the target readership. The study shows that while Strätling’s version appears to more adequately represent source text cultural knowledge and identity, it nevertheless still manages to perpetuate the exoticization of African culture as archaic, primitive, and inferior.